Orofacial Granulomatosis associated with Crohn's Disease a Multicentre Case Series - Phillips Frank (JOURNAL OF CROHNS & COLITIS, 2021)
Orofacial granulomatosis (OFG) is a rare syndrome that may be associated with Crohn's disease (CD). We aimed to characterise this relationship and the management options in the biologic era.This multicentre case series was supported by the European Crohn's and Colitis Organisation (ECCO), and performed as part of the Collaborative Network of Exceptionally Rare case reports (CONFER) project. Clinical data were recorded in a standardised collection form.This report includes 28 patients with OFG associated with CD: 14 males (mean age of 32 years, ±12.4 SD) and 14 females (40.3 years, ±21.0 SD). Non-oral upper gastrointestinal tract involvement was seen in 6 cases and perianal disease in 11. The diagnosis of OFG was made prior to CD diagnosis in 2 patients, concurrently in 8 and after CD diagnosis in 18. The distribution of OFG involved the lips in 16 cases and buccal mucosa in 18. Pain was present in 25 cases, with impaired swallowing or speaking in 6. Remission was achieved in 23 patients, notably with the use of anti-TNFs in 9 patients, vedolizumab in 1, ustekinumab in 1 and thalidomide in 2. A further 5 cases were resistant to therapies including anti-TNFs.OFG associated with CD may occur before, concurrently or after the diagnosis of CD. Perianal and UGI disease are common associations and there is a significant symptom burden in many. Remission can be obtained with a variety of immunosuppressive treatments, including several CD approved biologicals.